Analysis of Accounting Multipliers for the Mexican Economy - Ledesma-Carrión, Dora Elena; Hernández-Hernández, Lidia (Insights into Economics and Management Vol. 8, 2021)
For a country that for decades has grown around 2% annually, with loss of value chains and transformed into a country of services, with low wages and specialized labor in some economic activities and an overexploitation of natural resources in the last 40 years, requires an analysis of all productive activities. What are the economic activities with the largest direct accounting multiplier, which are the ones that most impact the households and in which income decile? And from the homes what is the most intensive economic activity? To answer these questions, we propose a social accounting matrix for Mexico, and from it, we obtain the accounting multipliers (direct, crossed and cyclical). In particular, cyclical accounting multipliers show that grocery and food wholesale activity is the most impacted from households. The activity with the largest direct multiplier is the manufacture of derivatives products of petroleum and coal (1.3295) followed by the mining of metallic minerals (1.1977), the manufacture of audio and video equipment (1.1846) and the manufacture of basic chemicals (1.1819). The total impact of the trajectory Manufacture of petroleum and carbon products -> Manufacture of basic chemical products -> Households -> Wholesale of groceries and food is between 0.0000575 and 0.0010816 for deciles 1 to 10.